(untitled) - Dullien, Sebastian (New York, 2004)
Sebastian Dullien gives a novel explanation for unemployment and inflation in the Euro-Zone. He argues that unemployment stems from a lack of cooperation between unions and monetary authorities: In an economy with endogenous money as EMU, wage setters are responsible for price stability while the central bank is responsible for the level of output. Cooperation between both actors is necessary for high employment and low inflation. The current institutional set-up is found to be unable to assure cooperation.
Keywords: Economic and monetary Union,Unemployment,Inflation (finance),Collective bargaining,Wages,Monetary policy,Banks and banking; European Union countries,European Union countries,European Union countries,European Union countries,European Union countries,European Union countries